Vertical disparities and perception of three-dimensional shape. - Cumming, BG; Johnston, E; Parker, A (1991)
The information about depth and three-dimensional shape available from the horizontal component of the stereo disparity field requires interpretation in conjunction with information about egocentric viewing distance (D). A novel computational approach for estimating D was proposed by Mayhew and Longuet-Higgins, who demonstrated that the horizontal gradient of vertical disparities uniquely specifies the viewing distance. We have now used random dot stereograms in a shape judgement task to show that changes in vertical disparities have no effect on perceived three-dimensional shape. Changes in ocular convergence do alter perceived shape, suggesting substantial changes in the subjects' scaling of horizontal disparities. We conclude that vertical disparities are not used to scale disparities for viewing distance, and that extraretinal signals must be considered when analysing human three-dimensional shape perception.